2011
DOI: 10.1209/0295-5075/94/18006
|View full text |Cite
|
Sign up to set email alerts
|

Aspiration-induced reconnection in spatial public-goods game

Abstract: Abstract. -In this Letter, we introduce an aspiration-induced reconnection mechanism into the spatial public goods game. A player will reconnect to a randomly chosen player if its payoff acquired from the group centered on the neighbor does not exceed the aspiration level. We find that an intermediate aspiration level can best promote cooperation. This optimal phenomenon can be explained by a negative feedback effect, namely, a moderate level of reconnection induced by the intermediate aspiration level induces… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
59
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(60 citation statements)
references
References 67 publications
0
59
1
Order By: Relevance
“…Inspired by the seminal paper introducing games on grids [18], evolutionary games on graphs and complex networks [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] have proven instrumental in raising the awareness of the fact that relaxing the simplification of well-mixed interactions may lead to qualitatively different results that are due to pattern formation and intricate organization of the competing strategies, which reveals itself in most unexpected ways. Specifically for the spatial public goods game [38,39], it has recently been shown that inhomogeneous player activities [40], appropriate partner selection [41,42], diversity [43][44][45], the critical mass [46], heterogeneous wealth distributions [47], the introduction of punishment [48,49] and reward [50], as well as both the joker [51] and the Matthew effect [52], can all substantially promote the evolution of public cooperation.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by the seminal paper introducing games on grids [18], evolutionary games on graphs and complex networks [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] have proven instrumental in raising the awareness of the fact that relaxing the simplification of well-mixed interactions may lead to qualitatively different results that are due to pattern formation and intricate organization of the competing strategies, which reveals itself in most unexpected ways. Specifically for the spatial public goods game [38,39], it has recently been shown that inhomogeneous player activities [40], appropriate partner selection [41,42], diversity [43][44][45], the critical mass [46], heterogeneous wealth distributions [47], the introduction of punishment [48,49] and reward [50], as well as both the joker [51] and the Matthew effect [52], can all substantially promote the evolution of public cooperation.…”
Section: Introductionmentioning
confidence: 99%
“…The standard way to realize this objective is to incorporate a stochastic element into the decision updating process. By using the Fermi function that is widely used in the studies of evolutionary game theory [21,[47][48][49][50], the probability of choosing to vaccinate for any individual i is defined as…”
Section: A Vaccination Decision Formation Processmentioning
confidence: 99%
“…After each time step, player x can reassess and imitate one of the more successful neighbor's strategies by comparing his/her payoff with that of a randomly selected neighbor y. Following previous studies [11][12][13][14]22,[33][34][35][36][37][38][39][40], player x can follow the strategy of a randomly selected neighbor y with the probability depending on the payoff difference (P x P y ):…”
Section: The Game Modelmentioning
confidence: 99%
“…Notably, increasing the number of neighbors n has a favorable effect on defection [35][36][37][38][39][40]. Our goal is to explore whether the effect of the size of the neighborhood n is beneficial for the maintenance of cooperation.…”
mentioning
confidence: 99%